2021
DOI: 10.3390/jcm10184089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Emergency on Life Activities and Delivery of Healthcare Services in the Elderly Population

Abstract: Due to the prevailing pandemic of the coronavirus disease COVID-19, we are experiencing emotional and social isolation, which negatively affects mental and physical health, particularly among the elderly population. In this study, we performed a cross-sectional analysis based on computer-assisted telephone interviews of 500 Polish adults aged 60 years or older in order to determine the impact of the SARS-CoV-2 pandemic on the older population’s behavior, life activity, and delivery of healthcare services. Acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Untreated for chronic diseases, COVID-19-infected patients are at an increased risk of death. Thus, despite the paradoxical sincere willingness to reduce the rate of SARS-CoV-2 transmission, such situations may adversely affect the clinical health of patients [ 12 ]. In this study, instead of highlighting the consequences of the fear during the COVID-19 pandemic (e.g., changes in behavior), we found subpopulations that are at the highest risk to exhibit health anxiety during the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Untreated for chronic diseases, COVID-19-infected patients are at an increased risk of death. Thus, despite the paradoxical sincere willingness to reduce the rate of SARS-CoV-2 transmission, such situations may adversely affect the clinical health of patients [ 12 ]. In this study, instead of highlighting the consequences of the fear during the COVID-19 pandemic (e.g., changes in behavior), we found subpopulations that are at the highest risk to exhibit health anxiety during the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…No compensation was provided for participating in the study. More details regarding the study design are shown in a previously published article [ 12 ]. The study was approved by the Bioethics Committee of Wroclaw Medical University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our recently published article [ 22 ], from a total of 500 respondents, 201 were concerned about COVID-19 infection (201/500; 40.2%). In contrast, only 18 respondents did not show any concerns about the pandemic (18/500; 3.6%, Table S4a ).…”
Section: Discussionmentioning
confidence: 99%
“…No compensation was provided for participating in the study. More details on the study design are presented in the previously published articles [ 22 , 23 ]. The study was approved by the Bioethics Committee of Wroclaw Medical University.…”
Section: Methodsmentioning
confidence: 99%